Spatial Distribution of Off-Host Stages of Tunga penetrans in the Soil within the Home Range of Nine Infected Dogs in An Endemic Tourist Area in Brazil - Anderson Vieira de Jesus; Anaiá da Paixão Sevá; Paula Elisa Brandão Guedes; Katharine Costa dos Santos; Tatiani Vitor Harvey; Gabriela Mota Sena de Oliveira; Thammy Vieira Bitar; Fernando Ferreira; George Rêgo Albuquerque; Renata Santiago Alberto Carlos (Tropical Medicine and Infectious Disease, 2023)
Tungiasis is a neglected disease caused by the sand flea Tunga penetrans, and dogs are considered the main reservoirs in Brazil. This study aimed to identify the role of dogs as tungiasis dispersers and to investigate the presence of T. penetrans in the soil of an endemic tourist area. Nine dogs infected by T. penetrans were included in this study and received GPS collars to analyze their movement through the village. Duplicate sand samples were collected in different areas of the community. Those areas were classified as peridomicile (n = 110), open area (n = 110), beach (n = 50), and river (n = 58). The analysis of the points recorded by the collars showed that the dogs roamed throughout the community, potentially facilitating the spread of the disease. Samples contaminated with developmental forms of the parasite were found in the circulation area of three dogs. Adult fleas were found in 3/328 samples. These data emphasize that infected dogs’ roaming can influence the fleas’ dispersion in the soil. Statistically, none of the study variables had a significant correlation (p > 0.5) with the presence of T. penetrans in the area analyzed. This study was the first to assess infected dogs’ role as tungiasis propagators.